Profil Motivasi Belajar Siswa SMP Pembangunan Laboratorium Padang - Arsida Nur; Suryadi Suryadi (Universitas PGRI SUMATERA BARAT, 2018)
This research is based on the researcher's awareness of the students who have low learning motivation that there are students who play in learning, lazy learning as disturbing his friends, telling when the teacher explained the lesson, playing Mobile, doodling his book that has nothing to do with lessons and doodling tables and student achievements that are still many under the minimum mastery criteria . This study aims to describe students' learning motivation. The sample in this study amounted to 210 students. This research is a research with quantitative descriptive approach. The result of this study shows that the students' learning motivation belongs to high category, based on the indicators of persistence in learning are in the high category, so the tenacious indicators are in high category, the interest indicator is in the high category and the independence indicator is in the category